On two new species of Schendylurus Silvestri 1907 from Venezuela, with redescription of S. colombianus Chamberlin 1921 and S. virgingordae Crabill 1960 (Chilopoda Geophilomorpha Schendylidae) - Pereira, Luis Alberto (1993)
Two new species of Schendylurus Silvestri 1907 are described, i.e., S. minutus n. sp. from Rancho Grande, Venezuela, and S. paolettii from Boconó, Venezuela. Two further species of the same genus are redescribed, viz., S. colombianus Chamberlin 1921 (after the holotype) and S. virgingordae Crabill 1960 (after a new specimen from the coralline bay Playa Mero, Morrocoy, State of Falcon, Venezuela, which has been compared with the type material). This latter species seems to be halophilous, probably distributed across oceanic spaces by rafting. A key is provided for the identification of the species of Schendylurus of Bolivia, Peru, Ecuador, northern South America, Central America and the West Indies.